2000
DOI: 10.1093/humrep/15.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sperm function of patients with myotonic muscular dystrophy

Abstract: Myotonic muscular dystrophy (MMD) is a genetic disease caused by a defective enzyme, myotoninkinase. Male patients with MMD are reported to have reduced fertility. The purpose of this work was to study sperm capacitation and acrosome reaction in the ejaculates of sterile males with MMD and of healthy males (control group). The expression of the specific D-mannose receptors was explored by microscopic examination and by flow cytometry analysis. In addition, the binding patterns of Pisum sativum (PSA) lectin to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Indeed, many studies found hypogonadism with sperm count defects (Hortas et al, 2000), testicular atrophy in 65.5% of patients (Vazquez et al, 1990) and damage to the seminiferous tubules as evident on biopsy specimens (Takeda and Ueda, 1977). In women, the correlation between fertility and MD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies found hypogonadism with sperm count defects (Hortas et al, 2000), testicular atrophy in 65.5% of patients (Vazquez et al, 1990) and damage to the seminiferous tubules as evident on biopsy specimens (Takeda and Ueda, 1977). In women, the correlation between fertility and MD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Infertile DM patients present with testicular atrophy, loss of libido and of potency [183]. Comparing sperms´ capacitation and acrosome reactions in the ejaculates of infertile DM patients and healthy men by different diagnostic tools (like the Pisum sativum and D-mannose receptor expression assays), a complete lack of capacitation and acrosome reaction of sperms from the DM patients has been diagnosed [184]. These anomalies therefore most likely cause the infertility of DM patients.…”
Section: Dystrophica Myotonica (Dm) Locusmentioning
confidence: 99%
“…A lack of association of DMPK genotype with fertility parameters is consistent with normal fertility for women carrying DMPK (CTG) 50 -150 repeats. 33,34 Although fertility can be compromised in males with mild or severe DM1, 16,35 the fathers in our study carried repeat sizes within the normal range, and therefore, no reduction in fertility due to (CTG) n repeat size would be expected in our study group.…”
Section: Discussionmentioning
confidence: 63%